Design and testing of inertia dynamometer for prototype fuel cell electric vehicle - Mohd Fakharuzi, M.H.A.; Syed Omar, S.M.H.; Ward, T.A.; Sheng, O.C.; Hanapi, S.; Sainan, K.I. (2014)
This paper describes and demonstrates the construction and the validation of a customized inertia dynamometer particularly designed for the UiTM urban fuel cell electric vehicle. The inertia dynamometer is designed to simulate real values of vehicle kinetic energy, acceleration resistance, rolling resistance and aerodynamic drag. Parameters used for calibration are taken from the actual road testing and calculated results. This dynamometer is equipped with two data loggers that are able to log voltage, current, speed and time which complement with gra phic user interface software for calculating torque and power. As final results, efficiency and energy consumption of the power train system can be calculated and analyzed.